Sugar signal mediates flavonoid biosynthesis in tea leaves. Issue 1 (14th March 2022) - Lv, Yi-Qing; Li, Da; Wu, Liang-Yu; Zhu, Yu-Meng; Ye, Ying; Zheng, Xin-Qiang; Lu, Jian-Liang; Liang, Yue-Rong; Li, Qing-Sheng; Ye, Jian-Hui
Abstract: Sugar metabolism and flavonoid biosynthesis vary with the development of tea leaves. In order to understand the regulatory mechanisms underlying the associations between them, a comprehensive transcriptomic analysis of naturally growing tea leaves at different stages of maturity was carried out. Based on weighted gene coexpression network analysis, the key gene modules (Modules 2 and 3) related to the varying relationship between sugar metabolism and flavonoid biosynthesis as well as the corresponding hub genes were obtained. KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis showed that the transcription factors (TFs) in Modules 2 and 3 were mainly enriched in the pathway of plant hormone signal transduction. An in vitro study showed that the transcriptional levels of ERF1B-like TF for hexokinase inhibitor and sucrose treatments were upregulated, being respectively 28.1- and 30.2-fold higher than in the control, suggesting that ERF1B-like TFs participate in the sugar-induced regulation of flavonoid biosynthesis. The results of yeast one-hybrid and dual-luciferase assays demonstrated that CsF3′H, encoding flavonoid 3′-hydroxylase, was the target flavonoid biosynthetic gene for CsERF1B-like TF. Our study identified the potential key regulators participating in the metabolism of sugars and flavonoids, providing new insights into the crosstalk between sugar metabolism and flavonoid biosynthesis in tea plants.